2013
DOI: 10.1080/09540121.2013.841835
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of middle-aged African-American women in the Deep South on antiretroviral therapy adherence

Abstract: Despite evidence of stabilization in some areas of the US, HIV infection in Black women is not declining in the Deep South. Using a phenomenological approach to qualitative inquiry, we investigated women's experiences influencing their adherence to HAART in an urban setting. Inclusion criteria specified Black women who had been aware of their HIV status for at least two years and were engaged in HIV outpatient care. Twelve single face-to-face confidential in-depth semi-structured interviews were conducted from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…This paper highlights the role of diverse "villages", including those of kinship, choice, and circumstance, that BWLWH identify as critical to their ability to overcome adversities across the lifespan. Dale and Safren's (2019) findings, informed by 45 in-depth qualitative interviews with BWLWH and community stakeholders, extend previous research (e.g., Dale, Pierre-Louis, Bogart, O'Cleirigh, & Safren, 2018;DeMoss, Bonney, Grant, Klein, del Rio, & Barker, 2014) in suggesting that social networks can help BWLWH better cope with HIV-related challenges. In particular, women reported about their positive experiences with communities that supported them in being their authentic selves, healthcare providers who prioritized empathy and compassion, and family members who provided "safe havens" from HIV-related stigma and adversity.…”
supporting
confidence: 59%
“…This paper highlights the role of diverse "villages", including those of kinship, choice, and circumstance, that BWLWH identify as critical to their ability to overcome adversities across the lifespan. Dale and Safren's (2019) findings, informed by 45 in-depth qualitative interviews with BWLWH and community stakeholders, extend previous research (e.g., Dale, Pierre-Louis, Bogart, O'Cleirigh, & Safren, 2018;DeMoss, Bonney, Grant, Klein, del Rio, & Barker, 2014) in suggesting that social networks can help BWLWH better cope with HIV-related challenges. In particular, women reported about their positive experiences with communities that supported them in being their authentic selves, healthcare providers who prioritized empathy and compassion, and family members who provided "safe havens" from HIV-related stigma and adversity.…”
supporting
confidence: 59%
“…Social networks and relationships can be enabling or motivating factors influencing health care outcomes such as retention in care and ART adherence in WLWH. The patient-provider relationship is often a salient factor positively associated with retention in care and ART adherence (DeMoss et al, 2014; Kempf et al, 2010; Messer et al, 2013; Tufts, Wessell, & Kearney, 2010; Webel & Higgins, 2012). In-depth interviews with 14 Black WLWH revealed that relationships with their providers positively influenced ART adherence (DeMoss et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The patient-provider relationship is often a salient factor positively associated with retention in care and ART adherence (DeMoss et al, 2014; Kempf et al, 2010; Messer et al, 2013; Tufts, Wessell, & Kearney, 2010; Webel & Higgins, 2012). In-depth interviews with 14 Black WLWH revealed that relationships with their providers positively influenced ART adherence (DeMoss et al, 2014). In addition to a positive patient-provider relationship in facilitating rapport, women in the rural Deep South reported wanting their providers to be caring and to inquire about their overall well-being (Boehme et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is necessary, though, to better understand the association between the photo-story process, how it helps women express transformation and change, and how the expression and/or transformation process may be related to health outcomes including both prevention and treatment outcomes [54]. The tentative explanations that we generated about how positive health, spirituality, self-acceptance and confidence transformations are related to women's health need to be tested more extensively to determine the association between photo-stories, transformation, and health behavior.…”
Section: Discussionmentioning
confidence: 99%